2006
DOI: 10.1523/jneurosci.2806-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Thrombin and Matrix Metalloproteinase-9 Exacerbates Neurotoxicity in Cell Culture and Intracerebral Hemorrhage in Mice

Abstract: The rapid loss of neurons is a major pathological outcome of intracerebral hemorrhage (ICH). Several mechanisms may produce the neurotoxicity observed in ICH, and these include proteolytic enzymes such as thrombin and matrix metalloproteinase-9 (MMP-9). We tested the hypothesis that thrombin and MMP-9 combine to injure neurons in culture and that they interact to promote the acute neurotoxicity that occurs in ICH in vivo. We report that human fetal neurons die when exposed to thrombin or MMP-9 in isolation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(135 citation statements)
references
References 51 publications
(62 reference statements)
4
131
0
Order By: Relevance
“…44 MMP-9 may contribute to the disruption of the blood-brain barrier, 43 aside from its ability to kill neurons. 77 In correspondence with these detrimental outcomes of MMPs early after SCI, the inhibition of MMP activity with GM6001 in the first three days of injury resulted in improvement in functional scores from 3 to 42 days after. 43 Interestingly, the same group reported that if the MMP inhibitor was used for the first seven days, rather than three days, long-term recovery of mice from SCI was attenuated.…”
Section: The Use Of Mmp Inhibitors In Acute and Chronic Cns Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…44 MMP-9 may contribute to the disruption of the blood-brain barrier, 43 aside from its ability to kill neurons. 77 In correspondence with these detrimental outcomes of MMPs early after SCI, the inhibition of MMP activity with GM6001 in the first three days of injury resulted in improvement in functional scores from 3 to 42 days after. 43 Interestingly, the same group reported that if the MMP inhibitor was used for the first seven days, rather than three days, long-term recovery of mice from SCI was attenuated.…”
Section: The Use Of Mmp Inhibitors In Acute and Chronic Cns Diseasesmentioning
confidence: 99%
“…For example, thrombin and MMP-9 combine to mediate the killing of neurons in the mouse brain in vivo, facilitated in part by the activation of MMP-9 by thrombin. 77 The interaction of MMPs with chemokines to alter trafficking of leukocytes into tissues has demonstrated the convergence of functions of two major classes of molecules (FIG. 1).…”
Section: When the Good Guys Go Badmentioning
confidence: 99%
“…Four coronal sections, approximately +2.0 mm to 0 mm from bregma, were cut on a freezing microtome and stored at −20°C in a cryoprotectant composed of 30% glycerol, 20% ethylene-glycol, and 50% PBS. Following three PBS rinses, the brain sections were stained using Hematoxylin & Eosin (Xue et al, 2006). These sections were scanned and analyzed with MCID elite software (Imaging Research, Linton, England).…”
Section: Measurement Of Histological Damagementioning
confidence: 99%
“…ICH activates thrombin, which is a major contributor to ICH induced brain injury (Xi et al, 2003a, Xi et al, 2006. Though thrombin is neuroprotective at low concentrations (Vaughan et al, 1995, Donovan and Cunningham, 1998, Striggow et al, 2000, Friedmann et al, 2001, Xi et al, 2003b, it is detrimental at high concentrations (Donovan et al, 1997, Xi et al, 2003a, Xue et al, 2006, Fujimoto et al, 2007. Direct infusion of 20U of thrombin into rat brain causes a lesion with brain edema formation and neuronal death (Fujimoto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation